DESAIN NOSEL ROKET CAIR RCX250 MENGGUNAKAN METODE PARABOLIK DENGAN MODIFIKASI SUDUT EKSPANSI - Eko Priamadi; Arif Nur Hakim; Romie O. Bura (Jurnal Teknologi Dirgantara, 2011)
The present research is conducted to design the optimum nozzles for RCX250 engine, that is designed to produce maximum thrust of 250 kgf with combination of LOX and Kerosene as its propellant. The new nozzles were determined to be parabolic nozzle, with conical nozzle as its comparison. The parabolic nozzle was designed using Thrust Optimized Parabolic (TOP) method invented by G.V.R.Rao. TOP nozzle design method is performed by approximating a Thrust Optimized Contoured (TOC) Nozzle using parabolic equation. The method would result more efficient nozzle than conical or ideal bell nozzle. Further, the parabolic nozzle were modified in its initial and exit angle to create uniform velocities distribution at nozzle exit. A Computational Fluid Dynamics Method (CFD) is used to simulate the nozzle designs. The simulation was carried out in axis-symmetric condition using commercial CFD software. The simulation results show that MOD 1 nozzle, with initial angle (θN) 26 deg and exit angle (θe) 12 deg, gives maximum thrust, which is 4.67 % higher than reference conical nozzle. Key words:Liquid rocket, Parabolic nozzle, Thrust, CFD